Epitope mapping and tagging by recombination PCR mutagenesis - Hatfield, C (BioTechniques, 1997)
We describe a rapid PCR method that directly inserts an epitope tag into an open reading frame (ORF) to facilitate protein detection. This project was performed within a varicella-zoster virus (VZV) system. In earlier work, we produced a monoclonal antibody (MAb 3B3) to one VZV ORF called gE. MAb 3B3 bound to its epitope under extreme denaturing conditions. To further characterize the epitope, we devised a technique that identified the epitope by its insertion into another protein of interest. The 3B3 epitope was mapped to 11 residues (residues 151-161; QRQYGDVFKGD) in the gE ectodomain by using the technique of recombination PCR. At the same time, the 3B3 epitope was inserted in-frame into another VZV protein for which no MAb was available. The end result, VZV gL3B3.11, was a unique construct possessing a 33-bp insertion that expresses gL-3B3 protein recognized by the MAb 3B3. The 3B3 epitope was verified to be both highly functional and stable. An important advantage of this recombination PCR method of epitope mapping and tagging is that the epitope sequence can be inserted anywhere along the nucleotide sequence of an ORF, regardless of existing restriction sites